Breadth and Depth of International Diversification: Interactions, Trade-offs and Profitability. (September 2013) - Li, Lee; Qian, Gongming; Qian, Zhengming
All firms have to decide on a strategic issue when they diversify into foreign markets: that is, what is the optimal level of the breadth and depth of diversification? In isolation, the breadth and the depth have been widely discussed in the existing business literature, but their relationships remain unknown. This study explores how the breadth and depth interact with each other to affect firm performance. Evidence collected in this study shows that the interaction effect is positive and significant when the level of both breadth and depth is moderate. When either dimension increases further, the interaction effect is still positive and grows even more significant. However, the positive and significant effect reverses and becomes negative (although non-significant) when a high level of both dimensions is reached. These relationships suggest that the adoption of an international diversification strategy should take into consideration breadth and depth simultaneously as they affect each other mutually in determining firm performance. Findings of the study shed light on an effective mechanism to design strategies in uncertain environments – an important issue in general management.